ส่วนประสมการตลาดที่มีผลต่อผู้บริโภคในกรุงเทพมหานคร เขตธนบุรีในการซื้อเครื่องสำอางนำเข้าจากประเทศเกาหลี - จิดาภา เรียบร้อย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This study aimed to study marketing mix affecting consumers in Khet Thonburi, Bangkok towards purchasing cosmetic products imported from Korea , including facial skincare product, in particular. Samples of this study were determined to 300 male and female consumers residing in Thonburi district, Bangkok who purchased imported Korean facial skincare product. Based upon the convenience sampling method being applied to this study, 100 samples were male while 200 samples were female. Questionnaires were used to collect data. Data analysis was done by the descriptive statistics, consisting of frequency, percentage and mean. Based upon the findings acquired from the 200 female samples and 100 male samples, most of them were single in the age of 21-35 years old with Bachelor’s degree. They worked as government officer/state enterprise employee and earned average monthly income at the amount of 15,001-30,000 Baht. Results of the study on the purchase of imported Korean facial skincare product revealed that source of information introducing and acknowledging the respondents about the studied product was magazine/journal. Type of imported Korean facial skincare product that they applied was mostly found in the category of day and night skincare. They had been applied the imported Korean facial skincare product for lesser than 6 months and reason in applying it was the desire to have young look/lessen wrinkles. The most favorite brand of imported Korean facial skincare product that the respondents applied was ETUDE HOUSE. They purchased it from the product counter or its standalone shop in the department stores. For the next purchase, they preferred to try on other brands. Frequency of purchasing the studied product was mostly found at once in 3 months. In each time of purchase, they spent around 1,001-2,000 Baht. Person influencing their decision towards purchasing imported Korean facial skincare product was friend. The purchasing opportunity was at the time when the existing product was finished. Results of the study on marketing mix affecting consumers in Thonburi district, Bangkok towards purchasing imported Korean facial skincare product, the respondents paid high level of concerns on product, price, place and promotion factors in orderly. In product factor, the first concern being ranked at high level was the product safety with non-allergenic and non-irritation; followed by the product fame and the clear information of manufacture and expiration dates, accordingly. In price factor, the first concern being ranked at high level was the reasonable price comparing to product quality; followed by the reasonable price comparing to product quantity and to other brands of product as imported from other countries, accordingly. In place factor, the first concern being ranked at high level was the availability of specific counter separated from other product brands; followed by the policy allowing consumers to take products by themselves without the assistance from the salesperson, and the beautiful, trendy and attractive decoration of product counter, accordingly. In promotion factor, the first concern being ranked at high level was the discount with attractive gift set; followed by service and additional knowledge given by the salesperson, as well as the product information offered by the salesperson at the certain selling location, accordingly